Metabolic Architecture of Acute Exercise Response in Middle-Aged Adults in the Community - Nayor, Matthew; Shah, Ravi V; Miller, Patricia E; Blodgett, Jasmine B; Tanguay, Melissa; Pico, Alexander R; Murthy, Venkatesh L; Malhotra, Rajeev; Houstis, Nicholas E; Deik, Amy; Pierce, Kerry A; Bullock, Kevin; et al. (Circulation (New York, N.Y.), 2020)
Whereas regular exercise is associated with lower risk of cardiovascular disease and mortality, mechanisms of exercise-mediated health benefits remain less clear. We used metabolite profiling before and after acute exercise to delineate the metabolic architecture of exercise response patterns in humans. Cardiopulmonary exercise testing and metabolite profiling was performed on Framingham Heart Study participants (age 53±8 years, 63% women) with blood drawn at rest (n=471) and at peak exercise (n=411). We observed changes in circulating levels for 502 of 588 measured metabolites from rest to peak exercise (exercise duration 11.9±2.1 minutes) at a 5% false discovery rate. Changes included reductions in metabolites implicated in insulin resistance (glutamate, -29%; =1.5×10 ; dimethylguanidino valeric acid [DMGV], -18%; =5.8×10 ) and increases in metabolites associated with lipolysis (1-methylnicotinamide, +33%; =6.1×10 ), nitric oxide bioavailability (arginine/ornithine + citrulline, +29%; =2.8×10 ), and adipose browning (12,13-dihydroxy-9Z-octadecenoic acid +26%; =7.4×10 ), among other pathways relevant to cardiometabolic risk. We assayed 177 metabolites in a separate Framingham Heart Study replication sample (n=783, age 54±8 years, 51% women) and observed concordant changes in 164 metabolites (92.6%) at 5% false discovery rate. Exercise-induced metabolite changes were variably related to the amount of exercise performed (peak workload), sex, and body mass index. There was attenuation of favorable excursions in some metabolites in individuals with higher body mass index and greater excursions in select cardioprotective metabolites in women despite less exercise performed. Distinct preexercise metabolite levels were associated with different physiologic dimensions of fitness (eg, ventilatory efficiency, exercise blood pressure, peak Vo ). We identified 4 metabolite signatures of exercise response patterns that were then analyzed in a separate cohort (Framingham Offspring Study; n=2045, age 55±10 years, 51% women), 2 of which were associated with overall mortality over median follow-up of 23.1 years ( ≤0.003 for both). In a large sample of community-dwelling individuals, acute exercise elicits widespread changes in the circulating metabolome. Metabolic changes identify pathways central to cardiometabolic health, cardiovascular disease, and long-term outcome. These findings provide a detailed map of the metabolic response to acute exercise in humans and identify potential mechanisms responsible for the beneficial cardiometabolic effects of exercise for future study.